2021
DOI: 10.3390/agronomy11040631
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Solar Cell (DSSC): Effects on Light Quality, Microclimate, and Growth of Orthosiphon stamineus in Tropical Climatic Condition

Abstract: The main challenge facing greenhouse designers is to achieve environment-appropriate greenhouses, especially in tropical regions. The excess radiant energy transmitted into the greenhouse predisposes plants to photo-inhibition and consequently reduces crop production. Lately, photovoltaic (PV) modules are equipped as a greenhouse rooftop to minimize the level of irradiation and air temperature in the greenhouse, simultaneously improving its energy consumption. Nevertheless, due to the low level of irradiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…In the performance-based evaluation method, the emphasis is given to quantifying the total building performance. The word 'Overall' in OTTV refers to all the components of heat gain combined together into a single quantity known as OTTV, namely conduction through the opaque wall (Qwc), conduction through the transparent glass (Qgc) and solar radiation through a glass (Qgsol) [17]. In Malaysia, study by Abdul Nasir and Hassan [16] suggested that, the heat conduction through opaque wall should be regulated between 0.2 to 5% from the calculated OTTV while the heat conduction through transparent windows account for 10 to 20% of the component of OTTV.…”
Section: Overall Thermal Transfer Value (Ottv)mentioning
confidence: 99%
“…In the performance-based evaluation method, the emphasis is given to quantifying the total building performance. The word 'Overall' in OTTV refers to all the components of heat gain combined together into a single quantity known as OTTV, namely conduction through the opaque wall (Qwc), conduction through the transparent glass (Qgc) and solar radiation through a glass (Qgsol) [17]. In Malaysia, study by Abdul Nasir and Hassan [16] suggested that, the heat conduction through opaque wall should be regulated between 0.2 to 5% from the calculated OTTV while the heat conduction through transparent windows account for 10 to 20% of the component of OTTV.…”
Section: Overall Thermal Transfer Value (Ottv)mentioning
confidence: 99%
“…From the perspective of greenhouse applications, DSSC cells are still in the research stage; the few studies available have focused only on the visible dye sensitization of the DSSC tiles [21]. N. Roslan et al used visible dye-sensitized solar modules as a shading device for a mini greenhouse and found out that DSSC shading lowered the interior heat by 1.47 • C and increased the relative humidity by 10.91% compared with the unshaded greenhouse and under normal ventilation [22,23]. In another study, L. Lu et al, using the same mini greenhouse configuration and the same DSSC modules sensitized with visible absorption dye, concluded that the temperature at the bottom surface of the DSSC is higher than that at the upper surface of the DSSC [24].…”
Section: Introductionmentioning
confidence: 99%
“…1−3 This makes DSSC a competent contender not only in replacing commercial silicon solar cells but also toward building integrated photovoltaic and agrivoltaic applications. 4,5 Typically, a DSSC consists of a mesoporous semiconductor photoanode sensitized with dye molecules, namely a photoanode, a platinum (Pt) counter electrode (CE), and a redox electrolyte. 6 Despite DSSC's maturity, its highest certified power conversion efficiency (PCE) stands at only 13% and depends on the following factors: (1) light absorption efficiency, (2) charge injection efficiency, and (3) charge collection efficiency.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Over the past few decades, solar photovoltaic (PV) technologies have gotten significant attention as renewable energy producers. Third-generation PV devices, particularly dye-sensitized solar cells (DSSCs), have been attractive due to their cost-effective components, flexible and lightweight design, high transparency, eco-friendliness, efficient charge carrier mechanism, and better performance in dim-light conditions when compared to other solar PV technologies. This makes DSSC a competent contender not only in replacing commercial silicon solar cells but also toward building integrated photovoltaic and agrivoltaic applications. , Typically, a DSSC consists of a mesoporous semiconductor photoanode sensitized with dye molecules, namely a photoanode, a platinum (Pt) counter electrode (CE), and a redox electrolyte . Despite DSSC's maturity, its highest certified power conversion efficiency (PCE) stands at only 13% and depends on the following factors: (1) light absorption efficiency, (2) charge injection efficiency, and (3) charge collection efficiency.…”
Section: Introductionmentioning
confidence: 99%